f(x) = x^2 /(x-2)

We know that if f= u/v , then f'= (u'v-uv')/v^2

Now we will assume that:

u= x^2 ==> u'=2x

v= x-2 ==> v' =1

Then f'(x) = [2x(x-2)- x^2(1)]/(x-2)^2

= (2x^2 -4x -x^2 )/(x-2)^2

= (x^2 -4x)/(x-2)^2

Now we will substitute with x=1

f'(1) = (1-4)/(1-2)^2

= -3/ 1= -3

Then f'(1)= -3

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now